SOCIALIZATION OF ANEMIA PREVENTION AMONG ADOLESCENT GIRLS IN SIGALOGO VILLAGE - Yohana Tetty Gultom; Astriana Fransiska Butarbutar; Lisnawati Tumanggor; Meta Agrifina (Outline Journal of Community Development, 2024)
Anemia is a condition in which the hemoglobin (Hb) level in the blood is lower than the normal range based on age and gender. Adolescent girls are at a higher risk of experiencing anemia because their growth requires higher nutritional intake, and other factors such as insufficient iron consumption, menstruation, medication, and tea consumption after meals can contribute to it. The negative impacts of anemia on adolescent girls include reduced immunity, impaired concentration in learning, decreased fitness, and decreased productivity. Community engagement activities aim to provide socialization about Anemia Prevention to adolescent girls in Desa Sigalogo, Tapanuli Utara Regency. The methods involved in these activities include needs identification, program planning, socialization implementation, and evaluation. The results of these activities demonstrate an improvement in the knowledge of adolescent girls regarding anemia and an increased awareness of the importance of prevention. They also performed well in the post-test, which measured their understanding after the socialization.